2022
DOI: 10.1007/s10875-022-01365-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to SARS-CoV-2 Infections in Children with Secondary Immunodeficiencies

Abstract: Background and Purpose It is a matter of research, whether children with immunodeficiencies are able to generate an effective immune response to prevent SARS-CoV-2 reinfection. This study aimed to evaluate and compare the seroconversion rates and changes of lymphocyte subsets during COVID-19 in immunocompetent children and those with secondary immunodeficiencies. Methods In 55 children — 28 immunocompromised and 27 immunocompetent — hospitalized with confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, Mahmoudi S et al found that lymphocytopenia rarely occurred in general children with mild infection of SARS-CoV-2, while lymphopenia mostly appeared in severe disease [ 11 ]. Kuczborska K et al found children have no tendency to lymphopenia, regardless of the severity of COVID-19 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Mahmoudi S et al found that lymphocytopenia rarely occurred in general children with mild infection of SARS-CoV-2, while lymphopenia mostly appeared in severe disease [ 11 ]. Kuczborska K et al found children have no tendency to lymphopenia, regardless of the severity of COVID-19 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The values of specific lymphocyte subsets are controversial. Several researches present higher ratio of CD4+/CD8 + T cell with more severity and greater lung involvement in both general [ 20 ] and immunocompromised children [ 12 ], suggesting decreased CD4+/CD8 + T cell ratios in children with immunocompromise may be a protective factor for the prevention for severe COVID-19. However, opposite opinions have reported higher CD8 + T cell level [ 21 ] and lower CD4+/CD8 + T cell ratio [ 11 , 21 ] have been seen in children with pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthy children are less likely to have severe COVID-19 compared to adults (4,5). Multiple studies have demonstrated worse COVID-19 infection outcomes and more severe disease in children who had received immunosuppressant medication or had an immunocompromising condition such as cancer compared to healthy children (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%